PENINGKATAN ANGKA PERCERAIAN SAAT COVID-19 DI PENGADILAN AGAMA JAKARTA SELATAN - Sunarto, Sunarto; Fadilah, Tubagus (Moderation | Journal of Islamic Studies Review, 2024)
Divorce is an emergency door that can only be passed in urgent circumstances. Therefore, Islam provides its final solution to married couples who experience disharmony in building their households, namely by divorce (talaq). The research on "The Increasing Divorce Rate During the Covid-19 Pandemic at the South Jakarta Religious Court" uses field research methods. This research can also be called case research or case study, with a qualitative descriptive approach. The object of this study is limited to certain months, namely April, May, June and July 2020. The conclusion of this research states, that: In the April-July 2020 interval there was a significant increase in divorce rates in the South Jakarta Religious Court, due to the Covid-19 pandemic. This is based on the following statistical data: In April there were 29 divorce cases, in May there were 43 cases, in June 436 cases and in July 705 cases. The main cause of divorce is due to economic factors, which can trigger commotion and constant disputes in the household.